Should University Presidents Have a Voice in Public Affairs? - Scott, Robert A. (International Higher Education, 2020)
During a period replete with falsehoods and misrepresentations expressed by prominent individuals, celebrities, and elected officials, who is to speak for truth? Who is to support scientific knowledge and the role of ethics, law, and science in guiding policy development? In the past, university presidents spoke out for truth and justice. This article explores why such voices are needed yet might be silent today.